Deep waters : the Ottawa River and Canada's nuclear adventure - Krenz, Kim, 1920- (McGill-Queen's University Press, 2004)
"Deep Waters is an account of the principal events and personalities involved in the successful development of the Canadian nuclear power system (CANDU), an achievement that is arguably one of Canada's greatest scientific and technical successes. Kim Krenz also describes the early history of Deep River, a town built exclusively for the scientists and employees of the Chalk River Project, and considers the impact of the Project on the traditional communities of the Ottawa Valley."--Jacket